Pengaruh Kualitas Sistem Informasi Akuntansi dan Teknologi Informasi terhadap Kinerja Perusahaan: Peran Mediasi Pengendalian Internal PT Semen Indonesia Distributor Distributor - Zulianda, Faisyatin; Suwandi Suwandi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Through improving company performance derived from all business activities, businesses can increase their competitiveness. This performance can run with procedures that can be completed with workers as data framework administrators. The effectiveness of a company's accounting information system is very important to support overall company performance and must meet high quality standards. This research uses a quantitative approach with analytical descriptive methods. The information source was gotten by finishing up a poll directed by representatives of PT Semen Indonesia Distributor 2023. Information obtaining will be examined utilizing SEM model with the assistance of the PLS program. The findings of a number of tests indicate that some aspects have a positive effect while others have a negative effect on each other. The quality of AIS has no effect on company performance but has a positive effect on internal control, while internal control and information technology have a direct positive effect on performance. Based on these results, it can be seen that improving the quality of AIS and information technology can basically improve company performance.